1998
DOI: 10.1074/jbc.273.47.31366
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisomal Δ3-cis-Δ2-trans-Enoyl-CoA Isomerase Encoded by ECI1 Is Required for Growth of the Yeast Saccharomyces cerevisiae on Unsaturated Fatty Acids

Abstract: We have identified the Saccharomyces cerevisiae gene ECI1 encoding ⌬ 3 -cis-⌬ 2 -trans-enoyl-CoA isomerase that acts as an auxiliary enzyme in the ␤-oxidation of (poly)-unsaturated fatty acids. A mutant devoid of Eci1p was unable to grow on media containing unsaturated fatty acids such as oleic acid but was proficient for growth when a saturated fatty acid such as palmitic acid was the sole carbon source. Levels of ECI1 transcript were elevated in cells grown on oleic acid medium due to the presence in the ECI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
87
1
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(90 citation statements)
references
References 58 publications
1
87
1
1
Order By: Relevance
“…We observed that recombinant PECI catalyzed the isomerization 3-cis-octenoyl-CoA to 2-trans-enoyl-CoA with a specific activity of 27 units/mg of protein. (7,8). We also assayed recombinant PECI for 2-enoyl-CoA hydratase and ⌬ 3,5 ,⌬ 2,4 -dienoyl-CoA isomerase activities (Table I) but were unable to detect these activities using crotonyl-CoA and 3,5-octadienoyl-CoA as the respective substrates.…”
Section: Identification Of Peci a Novel Mammalianmentioning
confidence: 99%
See 2 more Smart Citations
“…We observed that recombinant PECI catalyzed the isomerization 3-cis-octenoyl-CoA to 2-trans-enoyl-CoA with a specific activity of 27 units/mg of protein. (7,8). We also assayed recombinant PECI for 2-enoyl-CoA hydratase and ⌬ 3,5 ,⌬ 2,4 -dienoyl-CoA isomerase activities (Table I) but were unable to detect these activities using crotonyl-CoA and 3,5-octadienoyl-CoA as the respective substrates.…”
Section: Identification Of Peci a Novel Mammalianmentioning
confidence: 99%
“…However, we and others have recently identified and characterized the S. cerevisiae ⌬ 3 ,⌬ 2 -enoyl-CoA isomerase (7,8) and have found that this enzyme, Eci1p, shares few primary sequence features with MFE1. In this report we describe the identification and characterization of a novel, ubiquitously expressed mammalian peroxisomal ⌬ 3 ,⌬ 2 -enoyl-CoA isomerase (PECI) that is homologous to yeast Eci1p.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1A (2)(3)(4)(5). To metabolize evennumbered cis-double bonds in unsaturated fatty acids such as petroselinic acid (cis-C 18:1 (6) ), yeast rely on peroxisomal Sps19p (6) which corresponds to the auxiliary enzyme 2,4-dienoyl-CoA reductase (2,4-reductase) and peroxisomal Eci1p (7,8) representing the auxiliary enzyme ⌬ 3 -⌬ 2 -enoyl-CoA isomerase (3,2-isomerase; Fig. 1B).…”
mentioning
confidence: 99%
“…Protein species related to lipid metabolism were also up-regulated in pigs fed NSPEs. Of these proteins, mitochondrial δ3,δ2-dienoyl-CoA isomerase (ECI1) acts as an auxiliary enzyme in the β-oxidation of polyunsaturated fatty acids (Gurvitz et al, 1998). Histidine triad nucleotide binding protein 2 (HINT2) is positively responsible for regulating mitochondrial lipid metabolism and respiration in the livers of mice (Martin et al, 2013).…”
Section: Discussionmentioning
confidence: 99%